2014
DOI: 10.1519/jsc.0000000000000364
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Training-Induced Changes in Sprinting Speed and Sprint Momentum in Elite Rugby Union Players

Abstract: Speed and sprint momentum are considered to be important physical qualities for rugby. The purpose of the study was to understand the development of these qualities in senior and junior international rugby players. In part 1 of the study, a group of senior (n = 38) and junior (n = 31) players were tested for speed over 40 m. Initial sprint velocity (ISV), maximal sprint velocity (MSV), initial sprint momentum (ISM), and maximal sprint momentum (MSM) were calculated using 10-m splits. In part 2 of the study, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
83
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 18 publications
8
83
2
Order By: Relevance
“…Due to the trivial changes in speed, it can confidently be stated that improvements in maximal sprint momentum were most likely attributed to improvements in body mass. These changes have occurred in other rugby union and rugby league athletes of a similar age, with changes thought to be due to maturation and increased body mass of the player rather than large improvements in velocity (3,39).…”
Section: Anthropometric and Physical Changementioning
confidence: 96%
“…Due to the trivial changes in speed, it can confidently be stated that improvements in maximal sprint momentum were most likely attributed to improvements in body mass. These changes have occurred in other rugby union and rugby league athletes of a similar age, with changes thought to be due to maturation and increased body mass of the player rather than large improvements in velocity (3,39).…”
Section: Anthropometric and Physical Changementioning
confidence: 96%
“…Linear sprint testing is common for athletes (3,4,17,24,32). It is assumed that distances of 5 to 10 m can be used to assess an individual's ability to accelerate, while maximal velocities are considered to manifest between 20 and 40 m (3,4,32).…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that distances of 5 to 10 m can be used to assess an individual's ability to accelerate, while maximal velocities are considered to manifest between 20 and 40 m (3,4,32). While sprint time in isolation may not be considered a discriminate physical quality, it has been highlighted as influencing whether players start in Australian rules football (AFL), alongside measures of leg power, and high intensity running ability (32).…”
Section: Introductionmentioning
confidence: 99%
“…1 High levels of contact during match-play favour players with increased body mass, 2 whilst momentum is considered an important physical quality for successful performance. 3 Therefore, the movement and physical demands of match-play require high levels of aerobic capacity, speed and optimal body composition. 4 Physical testing of junior rugby union players has identified that high-intensity running ability, assessed via the 30-15 Intermittent Fitness Test (30-15IFT) 5 and Yo-Yo Intermittent Recovery Test Level 1 (Yo-Yo IRTL1) 6 does not increase with age.…”
Section: Introductionmentioning
confidence: 99%